Our 2015 approach to invasive pulmonary aspergillosis. Issue 6 (24th March 2015) - Liss, B.; Vehreschild, J. J.; Bangard, C.; Maintz, D.; Frank, K.; Grönke, S.; Michels, G.; Hamprecht, A.; Wisplinghoff, H.; Markiefka, B.; Hekmat, K.; Vehreschild, M. J. G. T.; et al.
Summary At the University Hospital of Cologne, in general two patient groups at high risk for invasive aspergillosis receive posaconazole prophylaxis: Acute myelogenous leukaemia patients during remission induction chemotherapy and allogeneic haematopoietic stem cell transplant recipients. Other patients at risk undergo serum galactomannan testing three times weekly. At 72–96 h of persisting fever despite broad‐spectrum antibiotics, or at onset of lower respiratory tract symptoms a thoracic computed tomography (CT) scan is performed. Without lung infiltrates on CT, IPA is ruled out. In lung infiltrates not suggestive for IPA mycological confirmation is pursued. In patients without posaconazole prophylaxis empiric caspofungin will be considered. CT findings typical for IPA prompt targeted treatment, and mycological confirmation. Bronchoalveolar lavage (BAL) is most important for cultural identification and susceptibility testing, and facilitates diagnosing other pathogens. BAL performance is virtually independent of platelet counts. If despite suggestive infiltrates BAL does not yield the diagnosis, CT‐guided biopsy follows as soon as platelet counts allow. Surgery can also be beneficial in diagnosis and treatment of IPA. If the diagnosis of IPA is not established, mucormycosis is a valid concern. In patients with breakthrough IPA during posaconazole prophylaxis liposomal amphotericin B is the drug of choice. If no posaconazole prophylaxis was given, voriconazole is the treatment of choice for IPA.